DISCRIMINANT ANALYSIS TOWARD DEMOGRAPHIC CHARACTERISTICS OF CIKAOBANDUNG VILLAGE COMMUNITY IN CITARUM HARUM PROGRAM - Diki Azis; Aulia Fashanah Hadining; Kusnadi Kusnadi (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2020)
The Indonesian Government through the Citarum Harum program formulates steps to control damage and pollution with various indicators of success, including placing the community around the river to behave in an environmentally friendly manner. The results of research on people's behavior intentions in the Citarum Harum program are influenced by various factors, but the demographic characteristics have not been studied whether each category of gender, age, latest education, and monthly income has clear differences in answering the questionnaire statement indicators and which indicators are make a difference. This research was conducted in RW 02, Cikaobandung Village with a discriminant analysis method. The results showed that there were no clear differences in the gender groups and there were clear differences between the group's latest educational characteristics, monthly income and age. Indicators that differ in age groups are IM2, last education is SN1, and monthly income is IM2, PN2 and BI1.